(untitled) (Proceedings of Southern Federal University. Philology, 2013)
Akimova E.N. Keywords: Russian language, multiethnic, multicultural, linguistics. This article focuses on the interregional conference "Russian language as the state language of the Russian Federation in the conditions of multiethnic and multicultural region." The very important issues were represented, such as the prospects of linguocriminalistics, the peculiarities of the Russian language in the modern media space, modern lexis of Russian language. Break-out sessions were dedicated to the specific features of Russian language in different regions of Russian Federation, innovations in Russian language study, the fiction language analysis, modern development of grammar and semantics of Russian language.